Mutagenic effect and antimutagenic potential of aqueous and methanol extracts from Hydrocotoyle bonariensis and Centella asiatica / Florinsiah Lorin - Lorin, Florinsiah (2015)
Mutations are the cause of innate metabolic defects in cellular system, triggering morbidity and mortality in living organisms. Since the mutagens are involved in the initiation and promotion of several human diseases, including cancer, the significance of novel bioactive phytocompounds in counteracting these pro-mutagenic and carcinogenics effects is now gaining attention. The aims of this study are to evaluate the phytochemical constituent, to determine the antioxidant capacity and to determine the mutagenic effect and antimutagenic potential in the absence and presence of metabolic activation (S9) in the plants extracts. In these study two samples namely H.bonariensis and C.asiatica aerial parts and roots in aqueous and methanol extracts were used to determine its bioactive compound via phytochemical screening and antioxidant capacity using the FRAP assay. Determination of the mutagenic effect and antimutagenic potential for both plants species were done using the Ames test after the bacterial strains fulfill the genotype characteristics needed. The finding revealed that both plants extract possessed alkaloid, phenol and tannins on its phythochemical content except for flavonoid which was only found in methanol extracts of H.bonariensis aerial parts. In the FRAP assay, both plants extracts showed antioxidant power. The results indicated that both methanol extracts of H.bonariensis aerial parts and methanol extracts of C.asiatica aerial parts and roots contain strong antioxidant power with high value of ascorbic acid equivalent. In the mutagenicity study, the methanol extracts of the aerial parts of H.bonariensis showed significant different (p<O.05) when compared to the negative control which shows positive response mutagenic effect at the concentration of 50 mg/ml with the mean number of revertant colony of 36.7 ± 6.4 for strain S.typhimurium TA 98 with the presence of metabolic activation (+S9). However, no mutagenic effect was observed by the roots of H.bonariensis in both extracts. On the other hand, the methanol extracts of the aerial parts of C.asiatica showed mutagenicity effect when tested in the presence of metabolic activation (+S9) by S.typhimurium TA 98 strain. The methanol extracts of the aerial parts of C.asiatica showed a significant difference (p<O.05) when compared to the negative control in all concentrations studied and also a dose-response relationship. The mean number of revertant colony at concentration of 50 mg/ml was 94.0 ± 2.6, 66.3 ± 7.8 for the concentration of 12.5 mg/ml and 38.0 ± 2.6 for the concentration of 3.125 mg/ml. No mutagenic effects were seen when treated with C.asiatica roots in both aqueous and methanol extracts. In contrast, both aerial parts and roots of H.bonariensis and C.asiatica in aqueous and methanol extracts exhibited an antimutagenic effect against direct mutagen. The strong antimutagenic effect was found in methanol extracts of C.asiatica aerial parts and roots against the direct mutagen in Sityphimurium TA 98 with the percentage of inhibition valued 64.39% and 67.80°A> respectively. In conclusion, both extracts of H.bonariensis and C.asiatica aerial parts and roots have alkaloid, phenol and tannins and also antioxidant capacity which possibly contribute to the antimutagenic potential against direct mutagen by both plants species. The mutagenic effect was only showed by the methanol extracts of aerial parts of H.bonariensis and C.asiatica in the presence of metabolic activation (+S9).